Development of a multi-unit floating drug delivery system by hot melt coating technique with drug-lipid dispersion - K. Chansanroj (2018)
A multi-unit floating drug delivery system containing pellets with lipid coating were fabricated. Coated pellets were prepared by a fluid bed hot melt coating technique with drug-lipid dispersion. Metoprolol tartrate was used as a water soluble model drug and hydrogenated soybean oil (HSO) was used as a lipid carrier. The drug was dispersed in molten HSO and the mixture was directly sprayed on inert nonpareils in a fluid bed chamber. No major interaction between drug and HSO was observed, nevertheless, the drug could be partially dissolved in the molten HSO. Increasing coating amount or adding an inert substance, Aerosil R972, in the coating mixture reduced the initial burst release as well as the total drug release. Increasing drug particle size gave a variation in the drug release due to brittle fracture induced at the nozzle by pressurized atomization air. Coated pellets presented a good floating property in vitro regardless of the coating amount. The present study shows that a drug-lipid dispersion coating prepared by a hot melt coating technique is a promising means for the development of multi-unit floating drug delivery systems.